2009
DOI: 10.1152/ajprenal.90760.2008
|View full text |Cite
|
Sign up to set email alerts
|

PP2B-dependent NO production in the medullary thick ascending limb during diabetes

Abstract: Calcineurin (PP2B) has recently been shown to be upregulated in the medullary thick ascending limb (mTAL) during diabetes. The mTAL expresses all three isoforms of nitric oxide synthase (NOS), which are subject to phosphoregulation and represent substrates for PP2B. Therefore, we hypothesized that diabetes induces PP2B-dependent upregulation of NOS activity and NO production in the mTAL. Three weeks after injection of streptozotocin (STZ rats) or vehicle (sham rats), mTAL suspensions were prepared for use in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 52 publications
4
23
0
Order By: Relevance
“…Nonetheless, WT mice had significantly greater NOS1, both the 160-and 130-kDa bands [two-way ANOVA, P ϭ 0.007 (160-kDa band) and P ϭ 0.014 (130-kDa band) for genotype]. The 160-kDa band for NOS1 [possibly the NOS1-␣ isoform (20)] appeared to be virtually absent in the KO mice, even with a longer exposure (Fig. 7A).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Nonetheless, WT mice had significantly greater NOS1, both the 160-and 130-kDa bands [two-way ANOVA, P ϭ 0.007 (160-kDa band) and P ϭ 0.014 (130-kDa band) for genotype]. The 160-kDa band for NOS1 [possibly the NOS1-␣ isoform (20)] appeared to be virtually absent in the KO mice, even with a longer exposure (Fig. 7A).…”
Section: Resultsmentioning
confidence: 97%
“…NOS1 (neuronal NOS or brain NOS) exists as a splice variant (NOS1-␣, NOS1-␤) (34) and is expressed in macula densa cells, TAL, and in cortical and medullary CD (29). NOS2 (inducible NOS) is found in TAL (20,32), and NOS3 (eNOS) is expressed in TAL and CD, in addition to renal endothelial cells (3,51).…”
mentioning
confidence: 99%
“…Whereas CnAa was considered to be the major isoform of the renal cortex with predominant expression in DCT, 13 we have confirmed that in TAL, CnAb is the dominant isoform. 27 Codistribution of CnAb with cyclophilin A and its paralogue, cyclophilin B, suggests that complexes composed of the calcineurin inhibitor CsA and one or both cyclophilin isoforms may form in TAL to locally inhibit CnAb phosphatase activity. 20 Calcineurin inhibitors may of course affect a variety of systemic and renal parameters via activation of the intrarenal renin-angiotensin system and modulation of the release of nitric oxide or endothelin-1.…”
Section: Discussionmentioning
confidence: 99%
“…Glomeruli were homogenized as described above with total protein determined by the Bradford method (BioRad Laboratories). Samples (20 g) were assessed by standard SDSpolyacrylamide gel electrophoresis followed by blotting to polyvinylidene difluoride membranes as described previously (Foster et al, 2009). All blots were incubated overnight with the following primary antibodies: integrin ␣ 3 antibody (goat polyclonal IgG) or integrin ␤ 1 antibody (rabbit polyclonal IgG).…”
Section: Downloaded Frommentioning
confidence: 99%